A novel tri-layered photoanode of hierarchical ZnO microspheres on 1D ZnO nanowire arrays for dye-sensitized solar cells. Issue 22 (9th February 2015) - Kang, Xiaohui; Jia, Chunyang; Wan, Zhongquan; Zhuang, Jia; Feng, Juan
Abstract : A novel tri-layered ZnO nanostructure, consisting of ZnO nanowires as the underlayer, small ZnO hierarchical microspheres as the interlayer and large ZnO hierarchical microspheres as the overlayer, was designed and studied as a photoanode for dye-sensitized solar cells. Abstract : A novel tri-layered ZnO nanostructure, which consists of ZnO nanowires (ZnO NWs) as the underlayer, small ZnO hierarchical microspheres (S-ZnO HMSs) as the intermediate layer and large ZnO hierarchical microspheres (L-ZnO HMSs) as the overlayer, was designed and studied as the photoanode for dye-sensitized solar cells (DSSCs). The photoanode was characterized by X-ray diffraction, scanning electron microscopy and its optical properties were measured by UV-vis spectrophotometry. The performance of the DSSC based on the photoanode was characterized by the incident-photon-to-current conversion efficiency (IPCE) and voltage–current curve ( I – V ). The results indicate that ZnO hierarchical microspheres show a good bifunctional character (light scattering effect and dye-loading ability), which causes the corresponding DSSCs based on the tri-layered ZnO photoanode to obtain the highest photovoltaic conversion efficiency (3.21%) compared with the DSSC based on the double layered ZnO photoanode and single layer ZnO NWs photoanode.